2014
DOI: 10.4161/15592324.2014.977200
|View full text |Cite
|
Sign up to set email alerts
|

Pollen tube growth: where does the energy come from?

Abstract: This review focuses on the energy metabolism during pollen maturation and tube growth and updates current knowledge. Pollen tube growth is essential for male reproductive success and extremely fast. Therefore, pollen development and tube growth are high energy-demanding processes. During the last years, various publications (including research papers and reviews) emphasize the importance of mitochondrial respiration and fermentation during male gametogenesis and pollen tube elongation. These pathways obviously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 95 publications
(129 reference statements)
0
75
0
1
Order By: Relevance
“…These analyses showed that pgd2-1 ovules can be fertilized by wild-type pollen tubes, and vice versa, pgd2-1 pollen tubes successfully compete for the fertilization of wild-type ovules. The latter is consistent with Suc (imported from stylar tissues; Leydon et al, 2014) being the primary energy source for pollen tube growth, mainly involving OPPP reactions in plastids (Selinski and Scheibe, 2014). However, pgd2-1 pollen tubes with (1) and Suc (2) gradients after centrifugation of 34 mL of crude extract, resulting in a band of purified peroxisomes (0.9 mL).…”
Section: Lack Of Homozygous Pgd2 Plants Is Linked To Missing 6pgdh Acmentioning
confidence: 52%
“…These analyses showed that pgd2-1 ovules can be fertilized by wild-type pollen tubes, and vice versa, pgd2-1 pollen tubes successfully compete for the fertilization of wild-type ovules. The latter is consistent with Suc (imported from stylar tissues; Leydon et al, 2014) being the primary energy source for pollen tube growth, mainly involving OPPP reactions in plastids (Selinski and Scheibe, 2014). However, pgd2-1 pollen tubes with (1) and Suc (2) gradients after centrifugation of 34 mL of crude extract, resulting in a band of purified peroxisomes (0.9 mL).…”
Section: Lack Of Homozygous Pgd2 Plants Is Linked To Missing 6pgdh Acmentioning
confidence: 52%
“…Accordingly, a proteomic study detected catalase (CAT3) and glutathione reductase (GR1) in developing pollen (Chaturvedi et al, 2013). Pollen and tapetum cells have also been shown to accumulate large numbers of mitochondria and show high rates of respiration (Lee and Warmke, 1979;Selinski and Scheibe, 2014). Under high temperatures, this might be expected to cause a dramatic increase in ROS.…”
Section: Reactive Oxygen Species Scavengingmentioning
confidence: 99%
“…Developing pollen and tapetum cells seem to have unusually high energy demands as indicated by their high numbers of mitochondria (Lee and Warmke, 1979;Selinski and Scheibe, 2014); depletion in carbohydrate reserves might thus affect tapetum and pollen more than other cells. However, experimental proof for the carbohydrate deficiency hypothesis is still lacking: Studies have not yet clarified whether reduced carbohydrate levels at elevated temperatures cause pollen abortion or merely reflect the consequence of reduced pollen functioning.…”
Section: Carbon Starvationmentioning
confidence: 99%
“…Pollen tubes are the fastest growing plant cells (Selinski and Scheibe, 2014). Pollen tubes grow by transferring chemical energy from stored starch and newly assimilated sugars into ATP (Rounds et al, 2011).…”
mentioning
confidence: 99%